People’s Multiparty Democracy: Marxist Foundation of Democracy and Human Rights - Pyakurel, Sushil (State, Society and Development: PMPD Perspectives, 2026)
Madan Bhandari’s People’s Multiparty Democracy (PMPD), adopted by the Fifth General Convention of the Communist Party of Nepal (Unified Marxist Leninist) (CPN [UML]), constitutes the programmatic framework of the Nepali revolution. It may be regarded as the culmination of four decades of the party’s accumulated experience since its establishment in 1949, and as the result of the creative application of Marxism within the specific conditions of Nepal. PMPD seeks to integrate socio-economic transformation with the principles of multiparty competitive democracy, civil liberties, human rights, and socialism. While classical Marxist-Leninist state theory prioritizes class power and the dictatorship of the proletariat, PMPD recognizes democracy and human rights as integral components of the socialist project. This article critically examines capitalist democracy on the theoretical basis of Marxist state theory, and analyzes the dimensions of socialist democracy, human liberation, human rights, and multiparty competition from a historical-materialist perspective. In addition, it discusses the democratic and human rights–oriented character of PMPD. The study draws upon the works of various Marxist scholars from around the world, the writings, reports, and proposals of Bhandari, as well as the author’s published and unpublished articles and writings. It also considers the efforts and experiences undertaken to establish democracy and human rights as the principal pillars of multiparty democracy. This article seeks to situate PMPD as a significant Marxist concept developed through the practical application of Marxism in Nepal, and to present it as a distinctive Marxist model of socialist transformation grounded in a competitive multiparty system.